2021
DOI: 10.7717/peerj.11599
|View full text |Cite
|
Sign up to set email alerts
|

A seven-lncRNA signature for predicting Ewing’s sarcoma

Abstract: Background Long non-coding RNAs (lncRNAs) are a class of non-coding RNAs with unique characteristics. These RNA can regulate cancer cells’ survival, proliferation, invasion, metastasis, and angiogenesis and are potential diagnostic and prognostic markers. We identified a seven-lncRNA signature related to the overall survival (OS) of patients with Ewing’s sarcoma (EWS). Methods We used an expression profile from the Gene Expression Omnibus (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…For example, Liu et al suggested that fetal-lethal noncoding developmental regulatory RNA (FENDRR) as an anti brotic long noncoding RNA can reduced pulmonary brosis by inhibiting broblast activation by reducing iron concentration, which may act as a potential therapeutic target for pulmonary brosis 16 . Aberrant expression of lncRNAs related with iron metabolism has been participated in regulating critical physiological functions which were linked to different types of cancer in present studies [17][18][19] . Moreover, a review revealed that hepatic iron accumulation can lead to brotic responses, and the signi cance and potential of iron-related proteins in the progression and development of liver brosis 20 .…”
Section: Introductionmentioning
confidence: 70%
“…For example, Liu et al suggested that fetal-lethal noncoding developmental regulatory RNA (FENDRR) as an anti brotic long noncoding RNA can reduced pulmonary brosis by inhibiting broblast activation by reducing iron concentration, which may act as a potential therapeutic target for pulmonary brosis 16 . Aberrant expression of lncRNAs related with iron metabolism has been participated in regulating critical physiological functions which were linked to different types of cancer in present studies [17][18][19] . Moreover, a review revealed that hepatic iron accumulation can lead to brotic responses, and the signi cance and potential of iron-related proteins in the progression and development of liver brosis 20 .…”
Section: Introductionmentioning
confidence: 70%
“…The increased expression of these seven lncRNAs was statistically correlated with poor overall survival [111]. These seven lncRNA, including SNHG17, WAC-AS1, LINC00623, SSBP3-AS1, and TDRG1, are yet to tested experimentally for their association and role in ES, although some have functional roles in other cancers [111]. This study opened a new research direction to explore the use of a set of ncRNAs as prognostic markers.…”
Section: Discussionmentioning
confidence: 94%
“…Just last month, a new study by Chen et al used machine learning and training models on existing RNA sequencing data sets from ES patients to identify a set of seven lncRNAs as prognostic risk marker for ES. The increased expression of these seven lncRNAs was statistically correlated with poor overall survival [111]. These seven lncRNA, including SNHG17, WAC-AS1, LINC00623, SSBP3-AS1, and TDRG1, are yet to tested experimentally for their association and role in ES, although some have functional roles in other cancers [111].…”
Section: Discussionmentioning
confidence: 99%
“…It should be noted that AUC greater than 0.7 is considered to have high accuracy of diagnostic model, while AUC greater than 0.6 is considered to have high accuracy of prognostic model. Several studies also showed that the accuracy of the prediction model is good based on AUC > 0.6 [30][31] . The area under the ROC curve of 1-5-year overall survival predicted in our study is greater than 0.6, indicating that the accuracy of the prediction model is good.…”
Section: Discussionmentioning
confidence: 99%